Advances in immunotherapy for colorectal cancer: a review. (May 2020) - Golshani, Gol; Zhang, Yue
Immunotherapy is a new and exciting modality of cancer treatments. Its role in gastrointestinal malignancies has been promising, especially in advanced disease. Although various therapies are available for treatment of advanced colorectal cancer, survival rates for these patients remain very poor. The application of immunotherapy in colorectal cancer has shown remarkable results for a subset of patients with mismatch-repair-deficient mutations or microsatellite instability in their tumors. This literature review evaluates the current role of immunotherapy in advanced colorectal cancer, potential challenges clinicians face with immunotherapy-based regimens, and the possible future approach of combined modality immunotherapy.